Pañcatantra : the book of India's folk wisdom - Olivelle, Patrick (Oxford world's classics (Oxford University Press), 1999)
The 'Pañcatantra' is the most famous collection of fables in India and was one of the earliest Indian books to be translated into Western languages. It teaches the principles of good government and public policy through the medium of animal tales.